Sustainable Architectural and Urban Morphology: A Case Study of Algerian Desert Palaces (KSOUR) Ksar Ouargla as A Model - Bouafia, Abderazak; Boudraa, Hocem Eddine (Indonesian Journal of Social Science Research, 2024)
The present study thoroughly examines the Ouargla Palace (Ksar Ouargla), with a particular focus on its urban and architectural dimensions. This research employs descriptive and analytical methodologies to elucidate the architectural and urban charac-teristics of Saharan palaces. Moreover, the study investigates the relationship between the urban fabric of Ksar Ouargla and its surrounding social, economic, and natural environments. A key objective is to compare the planning principles embedded in the urban and architectural framework of Ksar Ouargla with those proposed by prominent theorists such as Frey (1999), Williams (2000), and Barton (1999). These principles are evaluated in the context of achieving comprehensive sustainable development, emphasizing the alignment of urban development with the di-verse needs of the current population, while safeguarding the capacity of future generations to meet their own needs.